Effect of 2,4-D and TDZ on Callus and Shoot Induction from seed of Rice (Oryza stiva L.) cv. Sangyodphatthalung - Domyos, Premrudee; Domyos, Somporn; Chartikul, Meka; Saykawe, Jinarat (Journal of Vocational Education in Agriculture, 2020)
ABSTRACT The study aimed to investigate the effects of 2,4-dichlorophenoxy acetic acid (2,4-D) on callus induction and thidiazuron (TDZ) on shoot induction of rice (Oryza stiva L.) cv. Sangyodphatthalung. The sterilized seeds were cultured on Murashige and Skoog (MS) medium without and containing 1, 2 and 3 mg/L 2,4-D for callus induction. The experiment was done using completely randomized design (CRD), 10 replications. After 4 weeks of culture, it was found that calli were induced on all the MS medium supplemented with 2,4-D. The largest callus (1.09 cm in diameter) was found on the MS medium added with 2 mg/L 2,4-D with friable and creamy yellow. In the case of shoot induction, the sterilized seeds were placed on MS medium without and containing 1, 2 and 3 mg/L TDZ for 4 weeks. The results showed that shoots were successfully developed directly from embryo without intervening callus stage. Multiple shoots from culturing seed were enhanced by increasing the concentration of TDZ from 1 to 3 mg/L and the highest average number of shoots (7.00 shoots/seed) was observed on MS medium containing 3 mg/L TDZ. So, it can be concluded that 2 mg/L 2, 4-D was suitable for callus induction and 3 mg/L TDZ was suitable for shoot induction.